2016
DOI: 10.1097/pgp.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

GHRH Receptor Expression in Malignant Mixed Müllerian Tumors

Abstract: Malignant mixed Müllerian tumors (MMMTs) are aggressive malignant neoplasms with a high recurrence rate and poor prognosis. Despite advances in adjuvant therapies in recent years, the prognosis of these tumors has not improved. Growth hormone-releasing hormone (GHRH) is produced by a variety of malignant tumors and acts as a growth factor in an autocrine/paracrine manner. Its function requires the presence of its receptors to exert its effects on neoplastic cells. In this study, we evaluated the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…GH stimulates the production of the insulin-like growth factor I (IGF-I), which plays a major role in malignant transformation, metastasis and tumorigenesis in various cancers [36]. The presence of GHRH-R and its splice variants, on different types of cancer cell lines has been demonstrated [37][38][39]. In our study, we found association neither between GHRH-R expression and the HPV status, nor between GHRH-R expression and response to treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…GH stimulates the production of the insulin-like growth factor I (IGF-I), which plays a major role in malignant transformation, metastasis and tumorigenesis in various cancers [36]. The presence of GHRH-R and its splice variants, on different types of cancer cell lines has been demonstrated [37][38][39]. In our study, we found association neither between GHRH-R expression and the HPV status, nor between GHRH-R expression and response to treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…Process of which may promote endometrial proliferation and participate in the pathogenesis of ovarian, endometrial cancer and endometriosis. Another research shows that GHRH-R expresses in the majority of MMMT and this discovery could potentially serve as a basis for therapies using synthetic peptide antagonists of GHRH-R [23][24][25] . Additionally, positive estrogen receptor (ER) expression is detected in part of patients with uterine sarcoma.…”
Section: Discussionmentioning
confidence: 97%